De novo natural anti-M alloantibody emergence in severe Coronavirus Disease 2019. Issue 12 (December 2022) - Jeannet, Robin; Descazeaud, Alexandra; Daix, Thomas; Pauthier, Hélène; Pascal, Virginie; Hantz, Sébastien; Cam, Sophie Le; Francois, Bruno; Feuillard, Jean; Lafarge, Xavier
Abstract: The immune response is a key player in the course of SARS-CoV-2 infection, and is often seriously dysfunctional in severe Coronavirus Disease 2019. The hyperinflammatory status has been described to be accompanied by the appearance of autoantibodies. In a lethal COVID-19 infection, we observed the emergence of a de novo natural alloantibody which targeted the M antigen from the MNS blood group on red blood cells (RBC) without evidence of any cross-reaction with SARS-CoV-2 antigens. This IgM lambda alloantibody was unmutated and unswitched. Here, we describe for the first time the emergence of a bystander de novo natural alloantibody against RBCs in a severe COVID-19 patient, highlighting the extra-follicular humoral response reported in these cases.